Bridging carbon markets and agriculture: a comparative study of stakeholder engagement in South Korea and United States - Younghoo Cho; Ziwen Yu; Yiannis Ampatzidis (Discover Agriculture)
Abstract Agricultural stakeholder engagement remains one of the most persistent challenges in carbon market development, particularly for small- and medium-sized producers. This study investigates how institutional design influences the conditions under which these stakeholders can access, participate in, and benefit from agricultural carbon markets. Using a structured comparative framework, the study analyzes two contrasting models: South Korea’s centralized, state-led approach anchored by the Carbon Bank (CB) and Controlled Environment Systems (CES), and the United States’ decentralized, market-oriented framework exemplified by the USDA’s Partnerships for Climate-Smart Commodities (PCSC) and California’s Cap-and-Trade system. Four analytical dimensions guide the comparison: national policy inclusion, verification processes, stakeholder intermediation, and institutional scalability. The findings reveal that South Korea’s integrated architecture lowers participation barriers through standardized MRV (Measurement, Reporting, and Verification) systems and bundled public support, whereas the U.S. model promotes innovation and market interoperability but externalizes verification and outreach responsibilities, limiting inclusion. Rather than endorsing a singular model, the study proposes differentiated strategies: in the Global North, focus on expanding inclusive participation through unified digital infrastructure and diversified practice eligibility; in the Global South, prioritize verifiable, internationally compatible entry pathways to accelerate institutional learning and market access. By aligning carbon market structures with the needs and capacities of diverse agricultural actors, a hybrid infrastructure can enhance both the credibility and accessibility of future agricultural carbon markets.